2016
DOI: 10.1021/acs.jproteome.5b01069
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycoproteomics of Human Seminal Plasma Glycoproteins

Abstract: Seminal plasma aids sperm by inhibiting premature capacitation, helping in the intracervical transport and formation of an oviductal sperm reservoir, all of which appear to be important in the fertilization process. Epitopes such as Lewis x and y are known to be present on seminal plasma glycoproteins, which can modulate the maternal immune response. It is suggested by multiple studies that seminal plasma glycoproteins play, largely undiscovered, important roles in the process of fertilization. We have devised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 30 publications
0
50
2
Order By: Relevance
“…Bisected N-glycans terminated with Lewis X antigens are rare in humans. Interestingly, apart from pregnancy hCG described herein, sperm are the only reported human source of Insights into the hyperglycosylation of human chorionic gonadotropin substantial amounts of this family of glycans, which have been implicated in the inhibition of immune responses [50,51]. There have been many models presented to explain how the pregnant human female accommodates the foreign fetus during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…Bisected N-glycans terminated with Lewis X antigens are rare in humans. Interestingly, apart from pregnancy hCG described herein, sperm are the only reported human source of Insights into the hyperglycosylation of human chorionic gonadotropin substantial amounts of this family of glycans, which have been implicated in the inhibition of immune responses [50,51]. There have been many models presented to explain how the pregnant human female accommodates the foreign fetus during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…CLU has six possible n ‐glycosylation sites. Saraswat et al (2016) carried out extensive research concerning the presence and structure of human seminal plasma glycoproteins. In the report, the authors showed that CLU had four n ‐glycosylation sites.…”
Section: The Role Of Clu Glycosylationmentioning
confidence: 99%
“…They contained fucose, Lewis x /Lewis a , blood group H, or Lewis y /Lewis b oligosaccharide structures (Figure 1). In some regions of CLU, huge microheterogeneity was observed (Saraswat et al, 2016). We have not found any further data concerning glycans alterations in the seminal plasma CLU of infertile men so far.…”
Section: The Role Of Clu Glycosylationmentioning
confidence: 99%
“…The another study identified two protein biomarkers (ECM1 and TEX101) that can distinguish between non-obstructive and obstructive azoospermia with high sensitivity and specificity [ 124 ]. The latest analytical techniques enable measurement of post-translationally modified proteins – such glycoproteins in human seminal plasma [ 125 ] of which sialylated fibronectin was found to be associated with abnormal sperm parameters [ 126 , 127 ].…”
Section: Using Seminal Hormones As Diagnostic and Prognostic Tools Inmentioning
confidence: 99%